Peptide-Based Vaccine against SARS-CoV-2: Peptide Antigen Discovery and Screening of Adjuvant Systems - Ahmed O. Shalash (Pharmaceutics, 2022)
The SARS-CoV-2 virus has caused a global crisis, resulting in 0.5 billion infections and over 6 million deaths as of March 2022. Fortunately, infection and hospitalization rates were curbed due to the rollout of DNA and mRNA vaccines. However, the efficacy of these vaccines significantly drops a few months post immunization, from 88% down to 47% in the case of the Pfizer BNT162 vaccine. The emergence of variant strains, especially delta and omicron, have also significantly reduced vaccine efficacy. We propose peptide vaccines as a potential solution to address the inadequacies of the current vaccines. Peptide vaccines can be easily modified to target emerging strains, have greater stability, and do not require cold-chain storage. We screened five peptide fragments (B1–B5) derived from the SARS-CoV-2 spike protein to identify neutralizing B-cell peptide antigens. We then investigated adjuvant systems for efficient stimulation of immune responses against the most promising peptide antigens, including liposomal formulations of polyleucine (L10) and polymethylacrylate (PMA), as well as classical adjuvants (CFA and MF59). Immune efficacy of formulations was evaluated using competitive ELISA, pseudovirion neutralization, and live virus neutralization assays. Unfortunately, peptide conjugation to L10 and PMA dramatically altered the secondary structure, resulting in low antibody neutralization efficacy. Of the peptides tested, only B3 administered with CFA or MF59 was highly immunogenic. Thus, a peptide vaccine relying on B3 may provide an attractive alternative to currently marketed vaccines.